Early Versus Delayed Ventriculoperitoneal Shunt Placement For Hydrocephalus Associated With Myelomeningocele: A Systematic Review (Medical Forum Monthly, 2023)
Objective: The purpose of this systematic study is to assess the mortality results of early vs. delayed VP shunt implantation for hydrocephalus caused by myelomeningocele and examine early complication rates, 1-year follow-up data, shunt-related complications, shunt patency rates, and cerebellar dysfunction; and to determine the best practices for VP shunt placement in patients with hydrocephalus associated with myelomeningocele.Study Design: A Systematic ReviewPlace and Duration of Study: This study was conducted at the Department of neurosurgery, MMC Mardan, from June 2022 to June 2023.Materials and Methods: This systematic review was done in PubMed, Embase, and the Cochrane Library databases. The terms "hydrocephalus" OR "myelomeningocele" and "ventriculoperitoneal shunt" OR "VPS" were entered into the MedLine and Cochrane databases, respectively. The full text of the embedded articles was reviewed for inclusion criteria, relevance, and originality. The results of the included papers were combined using meta-analysis techniques, and their quality was assessed using the RAND Quality Assessment Tool (RAND-QAT).Results: According to the combined results of all studies in this systematic review, early VP shunt installation significantly decreased mortality and improved long-term outcomes (p 0.05) compared to delayed shunt placement. Furthermore, early shunt implantation preserved VP shunt patency for extended periods and was associated with a lower incidence of shunt-related complications (p 0.05). Moreover, patients in the early VP shunt group exhibited a reduced incidence of cerebellar impairment than those in the delayed group (p 0.05).Conclusion: The early VP shunt placement should be actively investigated for patients with hydrocephalus associated with myelomeningocele to minimize mortality, improve shunt-related complications, preserve shunt patency, and reduce cerebellar damage.